The superhero, icon of popular culture and intertext in Carlos Cortes' La última aventura de Batman - Arias Orozco, Grettel Mariana (2019)
Literature and Universal History have been full of diverse heroic characters. One of these characters is the Bat Man, who at a very young age witnesses the murder of his parents and, therefore, devotes his life to the fight against evildoers. Batman is an icon of popular culture and, in this story, it is a direct intertext of the imaginary of Gotham City and its masked hero. In The Last Adventure of Batman, by the Costa Rican writer Carlos Cortés, the author uses the figure of Batman as a means to unravel the mysterious origin of the protagonist. In this way, such detectives of the night, protagonist and Bat Man go into the darkness of the night and the unknown to undertake their latest adventure.